RANCANG BANGUN SISTEM INFORMASI MANAJEMEN PENGELOLAAN SARANA SEKOLAH BERBASIS WEB - Redempto De A.G. Cantana; Putu Wida Gunawan; Prastyadi Wibawa Rahayu (Jurnal Teknologi Informasi dan Komputer, 2025)
Facilities are an important component that determines whether a learning process is successful or otherwise. An effective learning process requires resources and media to support it. The current school facilities management data collection still uses conventional methods, so there are often errors in writing and inputting data into the book. The waterfall method, also known as a structured and sequential approach in software development, is used for this system because it allows users to participate in the planning process and produces a computerized system in a relatively short time. It is expected that this web-based information system will increase productivity, reduce data loss, and make recording school facilities easier.